Analysis of Gene Expression Profiling in Meningioma: Deregulated Signaling Pathways Associated with Meningioma and EGFL6 Overexpression in Benign Meningioma Tissue and Serum - Wang, Xuanchun (Public Library of Science, 2012)
Molecular mechanisms underlying the pathogenesis of meningioma are not fully elucidated. In this study, we established differential gene expression profiles between meningiomas and brain arachnoidal tissue by using Affymetrix GeneChip Human U133 Plus 2.0 Array. KEGG pathway analysis demonstrated that PI3K/Akt and TGFβ signaling pathways were up-regulated in fibroblastic meningioma, and focal adhesion and ECM-receptor interaction pathways were activated in anaplastic meningioma. EGFL6 was one of the most up-regulated genes in fibroblastic meningioma by microarray analysis. Quantitative real-time PCR demonstrated that benign meningiomas had significantly higher levels of EGFL6 mRNA than brain arachnoidal tissue and atypical and anaplastic meningiomas (P<0.001). EGFL6 gene was also highly expressed in ovarian cancer, but expressed lowly in other investigated tumors. ELISA analysis showed that patients with benign meningiomas and ovarian cancers had the highest serum levels of EGFL6 (mean concentration: 672 pg/ml for benign meningiomas, and 616 pg/ml for ovarian cancers). Healthy people and patients with other tumors, however, had low levels of serum EGFL6. In conclusion, we proposed that activation of PI3K/Akt and integrin-mediated signaling pathways was involved in the pathogenesis of benign and anaplastic meningiomas, respectively. We also presented evidence that EGFL6 was overexpressed in benign meningioma tissues and serum.